2016
DOI: 10.1186/s41038-016-0033-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic characteristics of death by burn injury from 2000 to 2009 in Colombia, South America: a population-based study

Abstract: BackgroundBurns are one of the most severe traumas that an individual can suffer. The World Health Organization (WHO) affirms that injuries related to burns are a global public health problem mainly in low- and middle-income countries. The first step towards reducing any preventable injury is based on accurate information. In Colombia, the basic epidemiological characteristics of burn injuries are unknown. The objectives were establishing the causes, high-risk populations, mortality rate, and tendencies of bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
0
10
0
3
Order By: Relevance
“…Low socioeconomic status gets compounded by lack of basic safety education into it becoming a major factor. 6,7 Electric burn still remains a considerable cause of morbidity in the developing parts of the world. 8 The damage to the tissues depends on the voltage of electricity and resistance of specific tissues, the current pathway and duration of contact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low socioeconomic status gets compounded by lack of basic safety education into it becoming a major factor. 6,7 Electric burn still remains a considerable cause of morbidity in the developing parts of the world. 8 The damage to the tissues depends on the voltage of electricity and resistance of specific tissues, the current pathway and duration of contact.…”
Section: Discussionmentioning
confidence: 99%
“…Rehabilitation of such patients is another issue which is beyond the scope of this study. 18 Mortality rates have been high among high voltage group (1-17%). We have noted an overall mortality rate of 10.5%.…”
Section: Discussionmentioning
confidence: 99%
“…This topic deserves additional consideration and further research. In addition, regarding the mortality rate of elderly patients with burns, the actual number of deaths caused by burns might be higher than reported in the literature because most studies only analyzed the mortality rate during hospitalization, and a certain proportion of the injured patients died at the scene of the burn or outside the hospital after completing treatment [43]. Duke et al [37] also observed an increase in the long-term mortality of elderly patients associated with burns, and the true mortality rate associated with burns would be underestimated if the rate only relies on hospital death data.…”
Section: E918537-8mentioning
confidence: 94%
“…This is consistent with the findings of Ghaderi and Attar 13 and a study in Columbia. 3 Lower accessibility of villagers to healthcare services is probably the reason for the higher rate of mortality resulting from burns in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…As the second leading cause of sudden death, second only to car accidents, burns are no doubt one of the most severe and one of the most serious health-threatening traumas. 1 - 3 The Physical and psychological consequences of burns affect not only the patients but also their families. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%